2018
DOI: 10.1590/18069657rbcs20170092
|View full text |Cite
|
Sign up to set email alerts
|

Clay Mineralogy of Subtropical Soils under Long-Term Organic Fertilization in No-Tillage Systems

Abstract: Organic fertilization effect on physical-chemical properties in no-tillage systems in tropical soils has been widely investigated, but little is known about the effects of this practice on the mineralogy of the clay fraction. This study aimed to evaluate the clay-fraction mineralogy of two subtropical soils, fertilized with organic residues in long-term no-tillage systems. An Alfisol fertilized with 0, 40, and 80 m 3 ha-1 yr-1 pig slurry was evaluated for eight years, and an Oxisol with 0, 8, and 16 Mg ha-1 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…The amplitude verified in the dataset, which was reflected in the calibration and validation models, is related to the lithological, climatic, geomorphological, and pedological diversity of the state of RS (Ministério da Agricultura. Departamento Nacional de Pesquisa Agropecuária, Brazil, 1973;Maluf, 2000;Streck et al, 2018) and was also observed in several other studies carried out in this state (Bertolazi et al, 2017;Coblinski et al, 2020;Da Silva, Fruett, Zinn, Inda, & do Nascimento, 2019;Moura-Bueno et al, 2019;Pedron, Lourenzi, Ceretta, Lorensi, & Cancian, 2018;Ramos et al, 2017).…”
Section: Discussionsupporting
confidence: 65%
“…The amplitude verified in the dataset, which was reflected in the calibration and validation models, is related to the lithological, climatic, geomorphological, and pedological diversity of the state of RS (Ministério da Agricultura. Departamento Nacional de Pesquisa Agropecuária, Brazil, 1973;Maluf, 2000;Streck et al, 2018) and was also observed in several other studies carried out in this state (Bertolazi et al, 2017;Coblinski et al, 2020;Da Silva, Fruett, Zinn, Inda, & do Nascimento, 2019;Moura-Bueno et al, 2019;Pedron, Lourenzi, Ceretta, Lorensi, & Cancian, 2018;Ramos et al, 2017).…”
Section: Discussionsupporting
confidence: 65%